2014
DOI: 10.3201/eid2008.140341
|View full text |Cite
|
Sign up to set email alerts
|

Levofloxacin-ResistantHaemophilus influenzae, Taiwan, 2004–2010

Abstract: Levofloxacin resistance in Haemophilus influenzae has increased significantly in Taiwan, from 2.0% in 2004 to 24.3% in 2010 (p<0.001). Clinical and molecular investigations of 182 levofloxacin-resistant isolates revealed that the increase was mainly the result of the spread of several clones in the elderly population in different regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
41
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 14 publications
4
41
1
Order By: Relevance
“…Although we found six small clusters, the majority of the strains were isolated from patients who had no relationship to each other. In a recent publication from Taiwan, regional clonal emergence was found in different areas of the country (35). None of the STs published in Taiwan were found in our study, suggesting that the evolution of FQresistant strains is regional (35).…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Although we found six small clusters, the majority of the strains were isolated from patients who had no relationship to each other. In a recent publication from Taiwan, regional clonal emergence was found in different areas of the country (35). None of the STs published in Taiwan were found in our study, suggesting that the evolution of FQresistant strains is regional (35).…”
Section: Discussioncontrasting
confidence: 53%
“…A recent surveillance study published in Taiwan showed a major increase in LVX resistance from 2% in 2004 to 24.3% in 2010 (35). In the United States in 2006, the percentage of FQ resistance was 0.1% (36), similar to the percentage found in Spain in 2011 (0.2%) (17).…”
Section: Discussionmentioning
confidence: 59%
“…Furthermore, the prevalence of BLNAR, BLPAR, and BLPACR were 62.4, 6.1, and 4.1% in other Japanese study [17]. The rate of levofloxacin-resistant was 24.3% in another Japanese report [18]. In South Korea, the rate of BLNAR, BLPAR, and BLPACR were 40.2, 9, and 24.6 [19].…”
Section: Discussionmentioning
confidence: 81%
“…Other species, such as Haemophilus spp. and ␤-hemolytic streptococci, have been less prone to becoming fluoroquinolone nonsusceptible but are emerging at high rates in some countries (25)(26)(27)(28)(29)(30)(31). Hampering the advancement of fluoroquinolones to include other more potent agents has been difficult, due to the safety profile observed for this class.…”
Section: Discussionmentioning
confidence: 99%